Simulation of Forces between Humid Amorphous Silica Surfaces: A Comparison of Empirical Atomistic Force Fields - Leroch, Sabine (American Chemical Society, 2012)
[Image: see text] Atmospheric humidity strongly influences the interactions between dry granular particles in process containers. To reduce the energy loss in industrial production processes caused by particle agglomeration, a basic understanding of the dependence of particle interactions on humidity is necessary. Hence, in this study, molecular dynamic simulations were carried out to calculate the adhesion between silica surfaces in the presence of adsorbed water. For a realistic description, the choice of force field is crucial. Because of their frequent use and transferability to biochemical systems, the Clay and CWCA force fields were investigated with respect to their ability to describe the water–silica interface in comparison to the more advanced Reax force field, ab initio calculations, and experiments.